Ethyl Chloroformate as Derivatizing Reagent for Gas Chromatographic Determination of Norephedrine, Ephedrine and Pseudoephedrine in Pharmaceutical Preparation - Abbasi. , K.; Khuhawar, M.Y.; Bhanger, M.I. (Asian Journal of Chemistry, 2010)
An analytical procedure has been developed for the gas chromatographic determination of norephedrine, ephedrine and pseudoephedrine using ethyl chloroformate as derivatizing reagent. Each of the compounds indicated single peak with mass spectrum corresponding to the derivative. The elution and separation was carried out from the column HP-5 (30 m × 0.32 mm i.d.) with film thickness 0.25 μm and detection was by flame ionization detector. The linear calibration curves were obtained with 47.5 to 475 μg/mL norephedrine, 50-500 μg/mL ephedrine and pseudoephedrine with detection limits of 11.2, 12.5 and 10 μg/mL, respectively. The method was applied for the determination of norephedrine, ephedrine and pseudoephedrine from pharmaceutical preparations and relative standard deviation (RSD) for the analysis of pharmaceutical preparation was obtained within 0.1 to 0.8 %. A number of additives present in the pharmaceutical preparations did not affect the determination. The % recovery of the norephedrine from pharmaceutical preparations was within 96.6-98.5 % with RSD 0.1-0.3%.